Educational achievement and traits emotional stability and agreeableness as predictors of the occurrence of backache in adulthood. (15th October 2017) - Cheng, Helen; Green, Andy; Chapman, Benjamin P.; Treglown, Luke; Furnham, Adrian
Abstract: This study investigated the associations between psychological as well as social factors in childhood and adulthood and the occurrence of adulthood back pain in a longitudinal birth cohort study. The analytic sample comprises 5698 participants with complete data on parental social class at birth, childhood cognitive ability tests scores at age 11, educational qualifications obtained at age 33, personality traits assessed at age 50, occupational levels, and back pain measured at age 55. Using hierarchical logistic regression analysis, results showed that among all socio-demographic and psychological factors examined, only the highest educational qualification (OR = 0.62: 0.41–0.93, p  < 0.05) and traits emotional stability (OR = 0.76: 0.71–0.83, p  < 0.001) and agreeableness (OR = 1.10: 1.01–1.21, p  < 0.05) were significant predictors of the occurrence of back pain in adulthood. No significant sex differences were found for the prevalence of back pain in adulthood. Highlights: 5698 participants with demographic and trait variables took part in a longitudinal study. Back pain measured at age 54 was the criterion variable. Education, emotional stability and agreeableness were significant predictors. No significant sex differences were found.